Corruption, seigniorage and growth: theory and evidence - Keith Blackburn; Kyriakos C. Neanidis; M. Emranul Haque (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper presents an analysis of the effect of bureaucratic corruption on economic growth through a public finance transmission channel. At the theoretical level, we develop a simple dynamic general equilibrium model in which financial intermediaries make portfolio decisions on behalf of agents, and bureaucrats collect tax revenues on behalf of the government. Corruption takes the form of the embezzlement of public funds, the effect of which is to increase the government's reliance on seigniorage finance. This leads to an increase in inflation which, in turn, reduces capital accumulation and growth. At the empirical level, we use data on 82 countries over a 20-year period to test the predictions of our model. Taking proper account of the government's budget constraint, we find strong evidence to support these predictions under different estimation strategies. Our results are robust to a wide range of sensitivity tests.
Keywords: E6; H6; O16; O17; O42; 330; Corruption; seigniorage; inflation; growth; Korruption; Steueraufkommen; Betrug; Münzgewinn; Inflation; Wirtschaftswachstum; Theorie; Schätzung; Welt